2017
DOI: 10.1177/1362361317728436
|View full text |Cite
|
Sign up to set email alerts
|

What do parents of children with autism expect from participation in research? A community survey about early autism studies

Abstract: Engagement with stakeholders is an essential part of the research process. This is particularly the case for early autism research with infant cohorts and their families, where a range of ethical issues are pertinent. Here, we report on a large survey of parents who have a child on the autism spectrum (n = 1040) which specifically probed attitudes to early autism research. The large majority of parents showed positive attitudes overall, and these were associated with greater access to services, higher service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…Participants preferring to talk to the researcher were interviewed via Skype or Zoom software. This virtual, face-to-face, direct engagement with parents via video-call accorded with research finding that parents of autistic children value direct contact with research teams (Fletcher-Watson, Larsen, & Salomone, 2019 ). The interview schedule featured 14 questions focussed on bilingualism, monolingual approaches and decision-making factors, and was administered in a semi-structured way, allowing interview discretion to follow up on certain points.…”
Section: Methodsmentioning
confidence: 57%
“…Participants preferring to talk to the researcher were interviewed via Skype or Zoom software. This virtual, face-to-face, direct engagement with parents via video-call accorded with research finding that parents of autistic children value direct contact with research teams (Fletcher-Watson, Larsen, & Salomone, 2019 ). The interview schedule featured 14 questions focussed on bilingualism, monolingual approaches and decision-making factors, and was administered in a semi-structured way, allowing interview discretion to follow up on certain points.…”
Section: Methodsmentioning
confidence: 57%
“…Historically, parents of autistic children have been listened to somewhat (Silverman and Brosco, 2007), and autistic people less so. Parents, like practitioners and third-sector workers, can advocate on behalf of their children and may often be stakeholders in research themselves – they should be included in the participatory agenda (Fletcher-Watson et al, 2017b). For this reason, we have referred throughout to engagement with both the autistic and the broader autism community.…”
Section: Introductionmentioning
confidence: 99%
“…22 Studies of parental reasons for allowing child participation in observational research also identified altruism and perceived personal benefit as reasons for participation, [23][24][25][26][27] along with reputation of, or trust in, the investigators or institution conducting the research. 28 Most were conducted outside the United States (US), and only two reported reasons for participation in autism spectrum disorder (ASD) or neurodevelopment research. 28,29 The few studies conducted in the United States have examined reasons within hypothetical or general health research, 28,30,31 biobanking for genetics research, [29][30][31][32] or focussed on specific medical conditions.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…28 Most were conducted outside the United States (US), and only two reported reasons for participation in autism spectrum disorder (ASD) or neurodevelopment research. 28,29 The few studies conducted in the United States have examined reasons within hypothetical or general health research, 28,30,31 biobanking for genetics research, [29][30][31][32] or focussed on specific medical conditions. 15,17 The range of reasons reported may be truncated because many studies provided only fixed-choice responses.…”
Section: Backg Rou N Dmentioning
confidence: 99%